Bibliometric analysis of IgA vasculitis nephritis in children from 2000 to 2022 - Luo, Fei; Li, Yuzhe; Zhang, Yuan; Song, Yehong; Diao, Juanjuan (Frontiers in Public Health, 2022)
Background IgA vasculitis Nephritis (IgAVN) is a kidney-damaging disease that occurs during the course of IgA vasculitis (IgAV) and is the most serious complication of IgAV. However, there is a lack of reports of bibliometric analysis of IgAVN in children. The purpose of this study is to conduct a bibliometric analysis of IgAVN in children from 2000 to 2022, to explore the current status and cutting-edge trends in the field of IgAVN in children, and to establish new directions for subsequent research. Methods Screening the literature in the field of IgAVN in children in the Web of Science Core Collection (WoSCC) from 2000 to 2022. Visual analysis of their annual publications, countries, institutions, authors, journals, keywords, and references were using CiteSpace5.8.R3 and VOSviewer1.6.18. Results A total of 623 publications were included in the study, since the beginning of 2014, there has been an overall increasing trend in the number of articles issued. The most prolific country and institution were China and Zhejiang University. The most frequently cited author was Coppo R, with 331 citations, who has made great contributions to IgAVN. Mao Jianhua, Lee JS and Wyatt Robert J were the most prolific authors, all with 9 articles. Pediatric Nephrology was the most published and cited journal. The highest burst strength keyword is IgA vasculitis, and the highest burst strength reference is Davin JC, 2014. Conclusion The research hotspots and trends predicted by the analysis of this study provide a reference for in-depth research in this field with a view to promoting the development of IgAVN research in children.